Inter-embodied parental vigilance; the case of child food allergy - Stjerna, Marie-Louise; Brady, Geraldine (Frontiers in Sociology, 2023)
There is developing interest in issues of embodiment in studies of children, health and illness. We take our point of departure in the parent-child-health/illness triad to explore the embodied aspects of parental vigilance in parenting children who have a food allergy, utilizing the concept of inter-embodiment. Drawing on a focus group study with parents in Sweden the analysis reveals that this vigilance can be seen as the embodied manifestation of concern for children's bodies in perpetual liminality, when constantly exposed to allergens and the risk of becoming ill. We argue that the lens of inter-embodiment, with a focus on bodies in relation, captures how parents lived experience of managing food allergy intertwines with that of their children in the parent-child-health/illness triad. The analysis uncovers a form of embodied knowledge that is often not verbalized, offering potential for new understandings of parent-child relations that center on chronic child health conditions.